Kieślowski, the mysteries of screens and God - Lis, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The computer seems like a privileged personage in Decalogue 1 (Dekalog, jeden, 1987/88, prem. 1989, dir. K. Kieślowski): it is used by Paweł and his father to solve mathematical questions about Miss Piggy, to calculate the durability of the ice on the pond, to know what Mum is doing, and to control domestic devices. For Kieślowski the computer is not just a gadget: Krzysztof ’s lecture describes its potential and its possible autonomy. Independent from man (the computer switches itself on), it becomes his rival: Kieślowski proposes a critical interpretation of the computer as a new idol, promising unlimited memory and knowledge. A similar preoccupation can be found in the Black Mirror series, where new technologies, existing or as yet still fantastic, are becoming more and more intrusive in the lives of their human protagonists. The computer seems also to be a rival of God, present in symbols in Decalogue 1: a sign of him is not only the metaphysical man played by Artur Barciś, but also the biblical symbol of fire and the Madonna’s tears.